Association between Apolipoprotein E gene polymorphism and the tortuosity of extracranial carotid artery - Wang, Jun-Wei; Li, Xin; Lu, Liu-Xi; Chen, Jun-Lin; Yang, Yong-Tao; Jin, Ge (Frontiers in Neurology, 2025)
BackgroundIt is widely recognized that the Apolipoprotein E (ApoE) exhibits a significant association with dyslipidemia and atherosclerotic cardiovascular disease (ASCVD). The tortuous extracranial carotid artery (ECA) is a frequently encountered vascular morphological anomaly that may be associated to ischemic cerebrovascular disease. The purpose of this study was to investigate the association between ApoE gene polymorphism and the tortuosity of ECA.MethodsThe clinical data and ApoE genetic test of inpatients who underwent head and neck DSA or CTA at our department between June 2020 and January 2024, were retrospectively analyzed. The tortuosity index (TI) of the ECA was measured and calculated. The included patients were analyzed using two grouping methods based on TI of the ECA: three groups determined by the tertile distribution and two groups based on the median distribution. Multivariate logistic regression analysis and Spearman rank correlation analysis were employed to investigate the correlation between ApoE genotypes and ECA tortuosity.ResultsA total of 238 patients were included in the study. The lowest tertile, the middle tertile and the highest tertile of TI distribution encompassed 91 cases (38.2%), 65 cases (27.3%) and 82 cases (34.5%) respectively. On the other hand, there were 127 cases (53.4%) in the low median group and 111 cases (46.6%) in the high median group. Due to the rarity of the three genotypes (ε2/ε2, n = 4; ε2/ε4, n = 1; ε4/ε4, n = 1), they were excluded for further statistical analysis. After adjusting for all covariates, the genotype ε3/ε4 continued to show an independent correlation with ECA tortuosity in the tertile groups (adjusted odds ratio = 0.469, 95% confidence interval: 0.242–0.969, p = 0.025). The Spearman’s rank correlation analysis revealed a significant negative correlation between the TI of ECA and ApoE gene polymorphism (in sequential order: ε2/ε3, ε3/ε3, and ε3/ε4) (rS = − 0.149, p = 0.023).ConclusionOur study suggested that the ε2 allele may be associated with the increased tortuosity of ECA, whereas the ε4 allele may leads to be a protective factor. The ε3 allele, as the most prevalent wild-type in human, has not exert a significant influence on ECA tortuosity.